2022
DOI: 10.1111/ped.14949
|View full text |Cite
|
Sign up to set email alerts
|

Invasive candidiasis in a neonatal intensive care unit in Fukuoka

Abstract: Background Invasive candidiasis (IC) is a leading cause of morbidity and mortality in preterm infants. The objective of this study was to determine the prevalence of IC infection in newborns in the neonatal intensive care unit (NICU) of a tertiary hospital in Japan, and to identify specific predisposing factors for IC. Methods We retrospectively collected data on demographics, clinical characteristics, and outcomes of infants with IC, who were discharged from a tertiary NICU in Japan between January 2009 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Unlike hospital-acquired systemic candidiasis, which is common in neonatal intensive care units worldwide, congenital systemic candidiasis is extremely rare and can occur in full-term and preterm infants. 1,2 A meta-analysis conducted in 2020 found that fewer than 50 recognized cases had been reported in the literature over the past 54 years. 2 The disease may be localized (i.e., congenital cutaneous candidiasis, CCC) and present as an extensive skin rash which eventually results in widespread desquamation, or generalized (i.e., congenital systemic candidiasis) which usually lacks cutaneous involvement and presents with respiratory distress, meningitis, sepsis, and death.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike hospital-acquired systemic candidiasis, which is common in neonatal intensive care units worldwide, congenital systemic candidiasis is extremely rare and can occur in full-term and preterm infants. 1,2 A meta-analysis conducted in 2020 found that fewer than 50 recognized cases had been reported in the literature over the past 54 years. 2 The disease may be localized (i.e., congenital cutaneous candidiasis, CCC) and present as an extensive skin rash which eventually results in widespread desquamation, or generalized (i.e., congenital systemic candidiasis) which usually lacks cutaneous involvement and presents with respiratory distress, meningitis, sepsis, and death.…”
Section: Introductionmentioning
confidence: 99%